MORPHOMETRY AND MORPHOTECTONIC OF CIANTEN AND CISAAT WATERSHED ON QUATERNARY VOLCANIC TERRAIN, GARUT, WEST JAVA - Sipahutar, Sumahang R.; Sukiyah, Emi; Sulaksana, Nana (Journal of Geological Sciences and Applied Geology, 2018)
The research area is located in the Baluburlimbangan, Garut regency, West Java Province.Geographically, the research area is located at 107° 52' 23.32" E - 107° 59' 30.04" E and 6° 57'28.21" S - 7° 3' 39.23" S. Research object comprise Cianten and Cisaat watershed which will becompared based on morphometric and morphotectonic parameters. Observations carried outdirectly in the field and data analysis carried out in the studio. Research result shows that researcharea can be classified into medium – weak active tectonic area. It is proved by bifurcation ratio(Rb), drainage density (Dd), and sinuosity of mountain front (Smf). Active tectonic condition is alsoindicated by geology structure formed in research area such lineament of ridge and valley, anddrainage pattern.Keywords: Cianten, Cisaat, morphometry, morphotectonic, watershed